Trichoptera Biodiversity of the Aegean and Adriatic Sea Basins in the Republic of Kosovo - Ibrahimi, Halil (J Insect Sci, 2014)
We present the first preliminary inventory of Trichoptera taxa in the Aegean and Adriatic Sea basins in Kosovo that have previously received poor and fragmentary attention. Adult caddisflies were collected using ultraviolet (UV) light traps in 13 stations in areas of the Aegean Sea and Adriatic Sea drainage basins in Kosovo. Nineteen species out of 82, reported in this article, are first records for the Kosovo caddisfly fauna. Five genera are recorded for the first time in Kosovo: Brachycentrus , Ecclisopteryx, Psilopteryx , Thremma , and Oecetis . During this investigation, we found several Southeastern European endemic and rare species whose previous known distribution was limited to particular areas of this region, as well as other species whose distribution is considerably enlarged by this investigation: Polycentropus ierapetra , Polycentropus irroratus , Chaetopteryx stankovici , Drusus schmidi , Drusus tenellus , Potamophylax goulandriourum , Oecetis notata , and Notidobia melanoptera . Even though this article is a result of a limited sampling effort, it increases the number of Trichoptera taxa recorded for the Republic of Kosovo to 131.